Neuronal dysfunction in individuals at early stage of schizophrenia, A resting-state fMRI study. (April 2023) - Ma, Xiaoqian; Yang, Winson Fu Zun; Zheng, Wenxiao; Li, Zongchang; Tang, Jinsong; Yuan, Liu; Ouyang, Lijun; Wang, Yujue; Li, Chunwang; Jin, Ke; Wang, Lingyan; Bearden, Carrie E.; et al.
Highlights: Individuals at ultra-high risk (UHR) for psychosis and drug-naïve first-episode schizophrenia (Dn-FES) patients exhibited local brain abnormalities, which involved in the central executive network (CEN) and ventral visual pathway (VVP). Hypoconnectivity in temporal-sensorimotor regions was observed among UHR and Dn-FES patients compared to HCs. A support vector machine (SVM) revealed the value of the fractional amplitude of low-frequency fluctuations (fALFF) in disease diagnosis and highlighted the importance of frontal and temporal alteration in the pathogenesis of schizophrenia. Cognitive impairments were found in both UHR and Dn-FES patients and fALFF values in the left ACC was negatively correlated with executive function among UHR individuals. Abstract: Schizophrenia has been associated with abnormal intrinsic brain activity, involving various cognitive impairments. Qualitatively similar abnormalities are seen in individuals at ultra-high risk (UHR) for psychosis. In this study, resting-state fMRI (rs-fMRI) data were collected from 44 drug-naïve first-episode schizophrenia (Dn-FES) patients, 48 UHR individuals, and 40 healthy controls (HCs). The fractional amplitude of low-frequency fluctuations (fALFF), regional homogeneity (ReHo), and functional connectivity (FC), were performed to evaluate resting brain function. A support vector machine (SVM) was applied for classification analysis. Compared to HCs, both clinical groups showed increased fALFF in the central executive network (CEN), decreased ReHo in the ventral visual pathway (VVP) and decreased FC in temporal-sensorimotor regions. Excellent performance was achieved by using fALFF value in distinguishing both FES (sensitivity=83.21%, specificity=80.58%, accuracy=81.37%, p=0.009) and UHR (sensitivity=75.88%, specificity=85.72%, accuracy=80.72%, p<0.001) from HC group. Moreover, the study highlighted the importance of frontal and temporal alteration in the pathogenesis of schizophrenia. However, no fMRI features were observed that could well distinguish Dn-FES from UHR group. To conclude, fALFF in the CEN may provide potential power for identifying individuals at the early stage of schizophrenia and the alteration in the frontal and temporal lobe may be important to these individuals.